Tinjauan Kritis Terhadap Ketidaksesuaian Standar Pelayanan Hotel Berdasarkan Perspektif Kebijakan Daerah dan Perlindungan Konsumen - Chandra, Niluh (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The hotel industry in Indonesia often faces problems related to service standards that do not meet consumer expectations. This discrepancy causes disputes that require effective resolution. This study analyzes the discrepancy in hotel service standards from the perspective of law and consumer protection, with a focus on the integration of local values in dispute resolution. The research method used is normative juridical with a qualitative approach. The results of the study indicate that law, such as the concept of Angkon Muakhi in Lampung society, can play a significant role in resolving hotel service disputes, so that harmonization between law and national law is important for effective consumer protection.